Environmental Quality in Industrial Areas: Case Study of a Company in Banyuasin Regency, South Sumatra Province - Bagas Pandu MURSANTO (PT Keberlanjutan Strategis Indonesia, 2026)
With the emergence of industry in the Banyuasin district area, especially in Gasing Village, there are more job opportunities for residents and Banyuasin residents. However, the industry's rapid growth in the Banyuasin district can also hurt the environment, including air and water pollution. This research was carried out through descriptive observations of environmental conditions at the case study site. Data is collected and evaluated based on environmental elements, especially ambient air, emissions, noise and wastewater. At the case study location at an agro-industrial company in the Banyuasin district, the quality of ambient air, noise, emissions and wastewater from the WWTP was tested, and samples were taken. The test results show that the quality of ambient air, noise, emissions and wastewater produced by the WWTP around the factory area is classified as good, and all parameters meet the standards. If the measurement results of this research are looked at, there is no critical threshold value that attracts attention. This research shows that the industry must monitor the quality of the environment to make improvements and reduce the company's negative impact on the environment and the surrounding community's health.